Patient safety benefits achieved through regulation in the international pharmaceutical field - Seppälä, Anni (My University, 2025)
The pharmaceutical field is a part of the broad healthcare sector and has made 1,700 billion revenue in the global market. However, the harm caused by medication errors and adverse effects is costly and common even though the pharmaceutical field is regulated by several different actors. The main research question of this thesis is “How can regulation of international business protect patient safety?” This thesis is a literary review, focusing on research on the pharmaceutical field and institutional theory. The pharmaceutical field is widely regulated, but the regulative forces depend on the country in question. On top of regulations there are other forms of organizations that direct the activities in the field, for example trade unions. When comparing the U.S. and Finland there are differences in how and what in the pharmaceutical field is regulated. Finland is part of the European Union which implements regulations that the member states need to abide by. Finland also has several other national regulative forces when in the U.S. the federal regulations are not as wide. Patient safety encompasses all the ways in which patients can be protected from harm. This includes storing medications according to requirements and providing necessary information. Patient safety should be in the fore front of practices in the pharmaceutical field. Regulating international business can cause pressure to change daily processes in a way that guards patient safety more effectively. Changes in processes protect patient safety when the changes aim to minimize the risks of human errors. The different levels of regulation aim to protect patient safety in different faces of the process.

Lääkeala on osa laajaa terveysalaa ja sen tuotot ovat noin 1 700 miljardia euroa kansainvälisesti. Kuitenkin lääkitysvirheiden aiheuttamat haitat ja lääkkeiden haittavaikutukset ovat kalliita ja yleisiä, vaikka lääkealaa säädellään usean eri toimijan kautta. Tutkielman pääkysymyksenä on ”Miten potilasturvallisuutta voidaan tukea sääntelemällä kansainvälistä liiketoimintaa?”. Tutkielma on toteutettu kirjallisuuskatsauksena, joka painottuu lääkealan ja institutionaaliseen teoriaan keskittyviin lähteisiin. Lääkeala säädellään laajasti, mutta sääntelevät tahot riippuvat tarkasteltavasta maasta. Sääntelyn lisäksi on muitakin organisaatioita, kuten ammattiliitot, jotka ohjaavat lääkealaa. Lääkealan sääntelyssä on maakohtaisesti eroja, kun tarkastellaan miten Yhdysvalloissa ja Suomessa lääkealaa säännellään. Suomi on osa Euroopan Unionia, joten kansallisen sääntelyn lisäksi Suomessa tulee noudattaa Euroopan unionin asettamia säädöksiä. Suomessa on useita sääntelyä toteuttavia kansallisia tahoja, kun taas Yhdysvalloissa liittovaltiotasoinen sääntely ei ole niin laajaa. Potilasturvallisuus kattaa kaikki keinot, miten potilaita voidaan suojata haitalta. Tähän sisältyy muun muassa lääkkeiden säilytys vaatimusten mukaisesti ja tarvittavan lääkeinformaation tarjoaminen. Potilasturvallisuus tulisi olla ensisijainen painopiste kaikissa lääkealan prosesseissa. Kansainvälisen liiketoiminnan sääntely voi luoda paineen muuttaa päivittäisiä prosesseja niin, että potilasturvallisuutta suojellaan tehokkaammin. Muutokset prosesseissa tukevat potilasturvallisuutta inhimillisten virheiden minimoimisen kautta. Eri sääntelyn tasot tähtäävät potilasturvallisuuden suojaamiseen jokaisessa lääkealan prosessissa.
Keywords: patient safety, regulations, international business pharmaceutical field, institutional theory, potilasturvallisuus, säädökset, kansainvälinen liiketoiminta, lääkeala, institutionaalinen teoria